Pengaruh Model Pembelajaran Cooperative Learning Terhadap Keterampilan Bermain Futsal dan Kerjasama (Team Work) Siswa SMA Al-Amanah Ciwidey - Bakti Purnama; Carsiwan; Asep Sumpena (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to analyze the effect of the Cooperative Learning model on futsal playing skills and teamwork ability among students of SMA Al-Amanah Ciwidey. The study used a quantitative approach with a pre-experimental method through a One Group Pretest-Posttest design. The sample consisted of 88 tenth-grade students selected through simple random sampling from a population of 432 students. The Cooperative Learning treatment was administered over 12 sessions, with measurements taken using the Game Performance Assessment Instrument (GPAI). Data were analyzed using the Paired Sample t-Test and N-Gain Score. The results showed that the Cooperative Learning model had a significant effect on futsal playing skills (t = -16.75; p = 0.000) with an N-Gain of 0.4875 (moderate category), as well as on teamwork (t = -6.07; p = 0.000) with an N-Gain of 0.2292 (low category). It can be concluded that the Cooperative Learning model is effective in improving both students' futsal playing skills and teamwork, although improvement in teamwork requires a longer learning duration for more optimal results. Keywords: Cooperative Learning, Futsal Playing Skills, Teamwork, Physical Education Learning